Case study: The role of milk in a dietary strategy to increase muscle mass and improve recovery in an elite sprint kayaker - Reid, K. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
Flatwater kayaking requires upper-body muscle strength and a lean body composition. This case study describes a nutrition intervention with a 19-year-old male elite sprint kayaker to increase muscle mass and improve recovery posttraining. Before the intervention, average daily energy intake was 13.6 ± 2.5 MJ (M ± SD; protein, 1.8 g/kg; carbohydrate, 3.6 g/kg), and the athlete was unable to eat sufficient food to meet the energy demands of training. During the 18-month intervention period, the athlete`s daily energy intake increased to 22.1 ± 3.8 MJ (protein, 3.2 g/kg; carbohydrate, 7.7 g/kg) by including milk-based drinks pre- and posttraining and before bed and an additional carbohydrate-based snack midmorning. This simple dietary intervention, along with a structured strength and conditioning program, resulted in an increase of 10 kg body mass with minimal change in body fat percentage. Adequate vitamin D status was maintained without the need for supplementation during the intervention period. In addition, the athlete reported the milk-based drinks and carbohydrate snacks were easy to consume, and no adverse side effects were experienced. This was the first time the athlete was able to maintain weight during intensive phases of the training cycle.